Effectiveness of Intercostal Stretch Technique on Pulmonary Conditions: A Narrative Review - Chowdhury, Kamrun Nahar (Journal of Pulmonology and Respiratory Research, 2024)
Background: The Intercostal Stretch Technique is one of the physiotherapy techniques that is used to solve different respiratory problems. It is used for increasing chest expansion and diaphragm excursion improvement and also intra-thoracic lung volume. Aim: The study aims to evaluate the effectiveness of the intercostal stretch technique. Methodology: A narrative review. In this study, an RCT study was used to review the intervention. Results: Several articles are used to discuss the effectiveness of the intercostal stretch technique. In stable COPD, diaphragmatic breathing and the intercostal stretch technique both work equally well to improve chest expansion and functional capacity while lowering dyspnea. Research has shown that IC stretch outperforms the anterior basal lift technique in lowering heart and respiratory rates while increasing oxygen saturation. According to this study, IC stretching in conjunction with breathing control may improve dynamic lung parameters, particularly FEV1/FVC%, more than breathing control alone. Patients with COPD have an increased functional exercise capacity and reduced dyspnea when aerobic training and respiratory muscle stretching are combined. Conclusion: Different articles demonstrated that IC stretch improved lung function, expired tidal volume, decreased dyspnea, and increased chest expansion.